2020
DOI: 10.5334/pb.564
|View full text |Cite
|
Sign up to set email alerts
|

Body Dissatisfaction as a Mediator between Identity Formation and Eating Disorder Symptomatology in Adolescents and Emerging Adults

Abstract: Eating disorder symptomatology generally develops during adolescence and emerging adulthood. Previous research has focused on the role of identity formation or body image in the development of eating disorder symptomatology, but integrative work is lacking. For this reason, the present cross-sectional study examined the mediating role of body dissatisfaction in the relation between identity formation and eating disorder symptomatology. Method: The sample comprised 659 participants between 15 and 30 years old (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…Finally, adolescents in moratorium and troubled diffusion-increasing exploration seemed more vulnerable to develop eating disorder symptoms (i.e., drive for thinness and bulimia). These results are in line with previous research (Palmeroni et al, 2020 ; Raemen et al, 2022 ), indicating that adolescents who are searching for a personal identity without making strong commitments may turn to eating disorder symptoms as identity substitutes.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Finally, adolescents in moratorium and troubled diffusion-increasing exploration seemed more vulnerable to develop eating disorder symptoms (i.e., drive for thinness and bulimia). These results are in line with previous research (Palmeroni et al, 2020 ; Raemen et al, 2022 ), indicating that adolescents who are searching for a personal identity without making strong commitments may turn to eating disorder symptoms as identity substitutes.…”
Section: Discussionsupporting
confidence: 92%
“…Because these adolescents lack a stable sense of identity when they begin to increasingly explore identity alternatives, they may be even more vulnerable to being guided by extrinsic goals and societal ideals, resulting in increased engagement in appearance comparison (Duriez et al, 2012 ). Subsequently, adolescents in these identity trajectory classes experienced higher levels of negative body image and lower levels of positive body image, confirming the established interplay between identity and one’s body image (Palmeroni et al, 2020 ; Verschueren et al, 2018 ). Interestingly, given that the interplay between identity and adolescents’ positive body image is still understudied, these findings suggested that identity formation indeed might be associated with one’s positive body image as well.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…It is estimated that 70%–80% of college-aged men (Hobza & Rochlen, 2009; Neighbors & Sobal, 2007) and 80%–90% of college-aged women struggle with their body image and weight (De & Chakraborty, 2015; Neighbors & Sobal, 2007). Students with body dissatisfaction are at higher risk for muscle-building supplement and steroid use (Brower et al, 1994; Eik-Nes et al, 2018), binge drinking, dieting (Eik-Nes et al, 2018), depression (Eik-Nes et al, 2018; Paxton et al, 2006), anxiety (Barnes et al, 2020; Regis et al, 2018), eating disorders and muscle dysmorphia (Almeida et al, 2021; Palmeroni et al, 2020), as well as low self-esteem (Paxton et al, 2006). In addition, many collegiate women and men engage in subclinical binge eating and dieting, and nearly one-third engage in compensatory behaviors such as excessive exercise (Lavender et al, 2010; Luce et al, 2008).…”
Section: Weight Concerns Scalementioning
confidence: 99%